Application For PLC using Sound Command - Faris, Rahma; Abdullah, Rawan; Dwaikat, Abdulhaleem (My University, 2020)
Our world is developing fast and our modern life needs to improve with that. Everyone is looking for speed and comfort with high quality, The sound is the second high speed in nature after the Light, we explain what we need by our Sound by our code, Imagine that we can turn lights on just by saying ' Turn Light on ', or we can Stop the Pump with another Sound command, we don't need wires or switches, Programmable Logic Controller is only what we need to make our life easy, save energy, save time, and achieve luxury. According to our research, this idea does not exist or it does not exist in the same technique That we decide to do, iPhone has Siri, Microsoft has Cortana, a designer using PLC to achieve this idea with Arduino or Digital signal processing but with Only PLC is the trick.